PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI ARTICULATE STORYLINE 3 PADA MATERI DAYS AND MONTHS KELAS IV DI MI ISLAMIYAH BANAT SENORI KABUPATEN TUBAN - Fithriyah, Dewi Niswatul; Habibullah, M. Romadlon; Istiqomah, Ayu Dwi (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2024)
Learning is the process of student interaction with learning resources in order to achieve a learning goal. Good learning is learning that is able to increase students' thinking power to be more critical, and able to foster student creativity. Rapid developments in the field of technology make the world of education have a new direction. In the past, education was only limited to education, but in the current era it has turned into edutaiment. The purpose of this research is to find out the development of interactive learning media at MI Islamiyah Banat Senori on grade IV English material. As well as to determine the feasibility validation of interactive learning media that has been developed on the material of days and months grade IV. Researchers use the R&D (research and development) research method. This type of research refers to development research. This research will produce a certain type of product which will then be tested for the effectiveness of the media that has been made. The products that have been produced are expected to be able to provide benefits to those who need them widely. This method consists of five stages, namely analyze, design, development, implementation, and evaluation. The learning media developed is an interactive-based articulate storyline 3 application for grade IV English subjects. The media can be used both in online and face-to-face learning. The percentage of trial scores at the pre-test stage was 54.7, while at the post-test stage was 86.3%. So it can be concluded that there is an increase in scores in each group after using interactive learning media that has been developed by researchers.